Úloha regulačních T buněk v protinádorové imunitní odpovědi - Klabusay, M (Klinicka onkologie, 2015)
Regulatory T-lymphocytes (Treg) are essential for regulation of immune homeostasis and prevention of autoimmune disease development. Regulatory T-cells prevent the onset of autoimmune diseases; they keep immune homeostasis and modulate immune response during infection. Their activity is precisely controlled. Regulatory T-cells belong to one group of immune cells, which can support tumor survival and growth. They realize their function through inhibition of effector T-cells and by regulation of tumor microenvironment through production of various soluble factors. Many publications have proven that the amount of Treg cells is elevated in both solid tumors and in hematologic malignancies. Nevertheless, little is known about mechanisms, which allow increase and maintenance of elevated Treg cells in cancer patients. In this review, we will focus, among others, on the description of function and phenotype of Treg cells, their modulation of humoral immune response and interaction with cancer stem cells. Current development of modern tumor immunotherapy allows new possibilities of influencing Treg cells function.
Keywords: Tumor Microenvironment; nádory; regulační T-lymfocyty; nádorové mikroprostředí; imunofenotypizace; Immunophenotyping; T-Lymphocytes, Regulatory; Humans; lidé; imunoterapie; Immunotherapy; Neoplasms